International Collaborative Study for the Calibration of a Proposed Reference Preparation for Thromboplastin, Human Recombinant, Plain - Tripodi, Armando; Chantarangkul, Veena; Negri, Barbara; Clerici, Marigrazia; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1998)
Stocks of the International Reference Preparation (IRP) for thromboplastin, human, plain, coded BCT/253 and held by the World Health Organization (WHO) are nearly exhausted and must be replaced. For practical reasons the choice of the replacement candidate was restricted to two available human recombinant preparations which were coded as X/95 and Y/95 and calibrated in an international collaborative study involving 19 laboratories from Europe, Australia, Canada and Argentina. To minimize the differences between routes of calibration, the two candidates were calibrated against the existing WHO-IRP from human, rabbit and bovine origin and the final ISI was the resultant average value. On the basis of predefined criteria (i.e., within- and between-laboratory precision of the calibration and the conformity to the calibration model), X/95 was the preferred candidate. The assigned ISI (SE of the mean) value is 0.940 (0.0060) and the interlaboratory coefficient of variation 4.7%.